2021
DOI: 10.1186/s13731-021-00176-2
|View full text |Cite
|
Sign up to set email alerts
|

Co-creation as an innovative setting to improve the uptake of scientific knowledge: overcoming obstacles, understanding considerations and applying enablers to improve scientific impact in society

Abstract: Impact-driven research is a EU priority and, increasingly, for universities around Europe. Still, there is need for specific strategies to improve the societal impact of scientific knowledge and therewith improve the uptake of scientific results. Co-creation deeply evolves the role of scientific knowledge and increases its impact. Albeit there is much research on the conceptualization and contextualization of co-creation, research on the microlevel dynamics of co-creation is less common. This article aims to u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The academic literature is more concerned with collaborations with industry (European Commission, 2021a). In general, research on cocreation through OS initiatives focuses on conceptualization rather than on deconstructing the collaboration dynamics between researchers, civil society, government, and industry (Stier and Smit, 2021). Aguinis et al (2020) used motivation theory to explain why there is a gap between the knowledge and practical application of OS and concluded that the perceived costs of openness are currently higher than the benefits.…”
Section: Open Relations Between Science and Societymentioning
confidence: 99%
“…The academic literature is more concerned with collaborations with industry (European Commission, 2021a). In general, research on cocreation through OS initiatives focuses on conceptualization rather than on deconstructing the collaboration dynamics between researchers, civil society, government, and industry (Stier and Smit, 2021). Aguinis et al (2020) used motivation theory to explain why there is a gap between the knowledge and practical application of OS and concluded that the perceived costs of openness are currently higher than the benefits.…”
Section: Open Relations Between Science and Societymentioning
confidence: 99%
“…This transformation has focused on social impact and co-creation, achieving relevant results for science and society (Girbes et al, 2022). The new Horizon Europe program aims to achieve and demonstrate to citizens that investment in scientific evidence has a clear return on improving the living conditions of societies (Stier and Smit, 2021). In 2010, the EC organized a large conference titled ‘Science against Poverty’ (EC, 2012).…”
Section: Sociology Before the Current Crisis Of The Scientific Progra...mentioning
confidence: 99%
“…Within this study, we combine the principles of the action research with the IM as they are closely related and foresee the active involvement of participants in the co-creation (Stier & Smit, 2021 ) and the ideation process (Hesmer et al, 2011 ; Meslec et al, 2020 ) of new values. This methodological approach allows better knowledge valorisation (Stier & Smit, 2021 ) to utilise the academic knowledge within the co-creation of the value innovation by application of IM methods.…”
Section: Theoretical Backgroundmentioning
confidence: 99%